SITES OF MESOZOIC VERTEBRATES ON THE TERRITORY OF LUGANSK REGION (UKRAINE) - Dernov, V.; Dernov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the work is to determine the state of study and the prospects for further research on the vertebrate animals remains from the Mesozoic deposits of the Lugansk region. To achieve this goal, collection and generalization of information on the locations of vertebral remains among the Mesozoic deposits of Lugansk region were made. Despite the considerable amount of findings of various groups of Mesozoic vertebrates remains in the Donets Basin territories adjoining them, their systematic and purposeful study, unfortunately, was not conducted in Lugansk region, although indications of the findings of the Mesozoic vertebrates remains in the Luhansk region occur quite often. As a result of the processing of published materials and preliminary interpretation of field observations, a list of 20 sites located mainly on the right bank of the Siversky Donets within the Lugansk region is compiled. Almost all the places are confined to the Upper Cretaceous deposits, much less – to the basal layers of the Paleogene and only one to the Triassic. The vast majority of the locations of the Upper Cretaceous are confined to the area in contact with an array of coal deposits (the so-called "open Carboniferous"). Outwards from it, the rocks are more open-sea and they drastically reduce the diversity of the fossil fauna. Therefore, outlining the range of promising areas regarding finding vertebrate animals remains one should be aware of the above-mentioned pattern of their placement. Triassic deposits of the Donbas are not at all investigated for finding the remains of vertebrates, although their potential is very significant. Nevertheless, due to the small area of the Triassic deposits outcrop in the Lugansk region, searches need to be directed to the west – in the Donetsk and Kharkiv regions.
Keywords: vertebrates; Lugansk region; Mesozoic; location